Multi-dimensional trust between partners for international online collaborative learning in the Third Space - McCollum, Brett; Morsch, Layne; Pinder, Chantz; Ripley, Isaiah; Skagen, Darlene; Wentzel, Michael (International Journal for Students as Partners, 2019)
The International Network for Chemistry Language Development is a community of faculty and students that employ video conferencing technologies in collaborative learning experiences. Learners partner with an international peer at another university to complete online collaborative assignments (OCAs). OCAs focus on shared learning and professional experience rather than assessment of knowledge to practice chemistry communication in the oral, written, and symbolic domains. We present OCAs as an example of the Third Space, where control over interactions and learning is negotiated between unfamiliar remote students, empowering students as emerging experts. This digital Third Space results in the formation of trust (a) between student partners to prepare for—and contribute during—the OCAs, and (b) between students and faculty as partners in teaching and learning. Additionally, we report how revisions to the OCA design are achieved with current students as consultants and partners, and former students as co-researchers and co-designers.